Cultivo de alface, sobre diferentes coberturas de solo, em condições tropicais - Paixão, Clodoaldo Moreno da (2013)
Lettuce is a leafy vegetable most produced in Brazil, however, there is still a need for studies aimed at improving the conditions of cultivation, which demands intense amount of fertilizer, degrades soil physical structure and biological causes imbalances by low rotation cultures. In production systems recommended for other species, the use of cover crops has been appointed as part of the solution to these problems. Thus, the aim of this study was to identify how the use of cover crops can contribute to improving the quality of lettuce produced in tropical weather conditions. The experiment was conducted in a randomized block design in a factorial design, with lettuce cultivation over five vegetable toppings solo deployed in three different eras. The cover crops used were millet, sugarcane bagasse, sugar cane, green manure, brachiaria grass and sunn hemp, sown on 06/02/12, 08/03/12 and 07/04/12. It was concluded that the use of plants covers may interfere with the soil properties and weed infestation, resulting in lettuce best quality. Lettuce plants with larger diameter and total dry mass were obtained when grown on waste velvet bean and brachiaria grass.